COPYRIGHT PROTECTION IN THE DIGITAL WORLD: A LEGAL FRAMEWORK FOR THE FUTURE - Savira Sekar Reynata; Rina Arum (Adisam Publisher, 2025)
This study aims to examine the legal framework and challenges in copyright protection in the digital era, where the dissemination and duplication of creative works occur rapidly and often without proper authorization. The main issue addressed is the increasing incidence of digital copyright infringement due to easy access and technological advancements, which ultimately harm content creators and weaken the authority of legal institutions. This research employs a qualitative method with a normative legal approach, through literature analysis, expert interviews, and the review of legal documents and digital regulations in Indonesia. Data were collected from academic publications, legal documents, and government reports, then analyzed using content analysis techniques. The results of the study indicate that Indonesia's legal framework, although governed by Law No. 28 of 2014, is still insufficient to address the complexities of digital copyright violations. A future-oriented legal strategy needs to integrate Digital Rights Management (DRM) technology, blockchain-based verification, and educational programs to enhance legal literacy. Strengthening copyright protection not only preserves the integrity of creative works but also supports the sustainability of Islamic education in the digital age.